Disease related variables and psychological problems among chFonically ill children in Malaysia - Azizah, Othman (Pusat Pengajian Sains Perubatan, 2010)
Aims: The study examines disease reiated variables that may exacerbate psychological problems among children with chronic illness in Malaysia. Methods: Parents' ratings of children behavioral and emotional problems (i.e. Child Behavior Checklist - CBCL), disease-related and socio-demographic information were obtained from 63 parents of children suffering from cancer. epilepsy, and asthma seen in Institute of Pediatrics, Kuala Lumpur General Hospital. Results: The results showed positive and significant relationship between frequency of hospitalization and a later onset of illness and psychological problems in children. Children in the age group of 7-11 years were reported to have the highest number of problems as compared to other age groups. There were no significant relationships between duration of illness, children's gender, number of siblings, and number of years attending school and psychological problems in children. Recurrent hospitalization and the onset of disease in the later childhood are amongst the most potent factors contributing toward the psychological problems of chronically ill children. There is an urgent need to further develop existing children and adolescent health facilities in Malaysian hospitals by directly involve mental health experts and promoting their services to both medical practitioners and service recipients.